(untitled) (Tempo e Argumento, 2021)
What is the relationship between the ideals of an egalitarian community in the beginning of the 20th century and children’s drawings in the 21st century? Is it possible to address the History of the Present Time from the perspective of a suspended time, which is neither a process nor a repetition? Through the testimony of a German friar, made in 1913, and 3 children’s drawings produced in 2020, both about the Santa Irmandade do Contestado, I propose to think through the possible connections between history of the present time and Walter Benjamin’s categories called ‘now-time’ (Jetztzeit) and ‘dialectical image.’ My assumption is that the ideals of the Santa Irmandade do Contestado reappear in children’s drawings produced by school students in one of the municipalities that were the ground of the conflict. Finally, I propose to expand the repertoire of analysis and reflections on the multiple temporalities that go through what, in the French historiographic tradition, has been called History of the Present Time. Keywords: Now-time; history of the present time; dialectical image; history teaching; Contestado War.